2002
DOI: 10.1093/biomet/89.3.603
|View full text |Cite
|
Sign up to set email alerts
|

A simple and efficient simulation smoother for state space time series analysis

Abstract: This document contains my notes relating to the paper, "A simple and efficient simulation smoother for state space time series analysis", by Durbin and Koopman(2002).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
509
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 539 publications
(510 citation statements)
references
References 8 publications
0
509
0
1
Order By: Relevance
“…de Jong and Shephard (1995) and Durbin and Koopman (2002) have developed simulation smoothing methods for sampling α from g(α|y * ; ψ) in a computationally efficient way. The Kalman filter calculates g(y * ; ψ) via its evaluation of the likelihood function for the linear state space model (A.4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…de Jong and Shephard (1995) and Durbin and Koopman (2002) have developed simulation smoothing methods for sampling α from g(α|y * ; ψ) in a computationally efficient way. The Kalman filter calculates g(y * ; ψ) via its evaluation of the likelihood function for the linear state space model (A.4).…”
Section: Resultsmentioning
confidence: 99%
“…Two strategies allow us to improve the efficiency of f . First, we use antithetic variables for variance reduction; see for example Durbin and Koopman (2002). Second, we note that observations far in the past add little or no information about the current state α t , but contribute to the variance of the importance weights ω s .…”
Section: (B3)mentioning
confidence: 99%
“…Third, because the method does not require any auxiliary simulation (c.f. Durbin and Koopman, 2002), it is scalable as the size of t y grows.…”
Section: Efficient Estimation Of the Latent Statesmentioning
confidence: 99%
“…The methods are carefully reviewed in Kim and Nelson (1999) and Durbin and Koopman (2001) and the basic recursions are briefly summarised in Appendix A. Important further refinements of the simulation approach are offered in de Jong and Shephard (1995), using the distribution of the errors in the model and in Durbin and Koopman (2002), using auxiliary data samples. Another sampling improvement was recently introduced by , who suggested that because t G and t η enter multiplicatively in equation (1), they should be sampled jointly.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative algorithms are provided by Carter and Kohn (1994), De Jong and Shephard (1995), Durbin and Koopman (2002), Frühwirth-Schnatter (2004) and Strickland, Turner, Denham, and Mengerson (2009). PySSM contains a simulation smoothing class, which uses the most computationally efficient, of the aforementioned simulation smoothing algorithms, given the specified SSM.…”
Section: Bayesian Estimation Of Ssmsmentioning
confidence: 99%